Pelatihan Kepemimpinan dan Kerja Sama Tim dalam Peningkatan Keterampilan Berorganisasi bagi Generasi Muda Tangerang Selatan - Muda, Yogi Prima (Yayasan Kawanad, 2025)
This Community Service Program aims to develop organizational skills among young generation in South Tangerang through structured approach based on direct experience. The activity was designed to provide theoretical understanding and practical skills that students can apply in daily life. Interactive methods such as group discussions, simulations, and role-playing were used to help students understand leadership concepts and teamwork as well as how to apply them in organizations. Training participants consisted of 80 high school and vocational school students from 10 schools in South Tangerang who serve as student council members. The program was conducted on February 24, 2025, at SMK Negeri 2 South Tangerang. Evaluation results showed significant improvement with average post-test scores increasing by 25% compared to pre-test, and 90% of participants stated that the activity was very beneficial. The participatory and interactive approach successfully fostered organizational spirit, enhanced leadership capabilities, and strengthened effective teamwork culture. Supervising teachers reported that participants became more active in student council activities and extracurricular programs after the training. The program is expected to continue with broader coverage and collaboration with other schools in South Tangerang to strengthen the role of young generation as agents of change capable of facing global challenges.